Research into Correlation between the Lubrication Mode of Contact Surfaces and Dynamic Parameters of Turbo-Generator Transmissions - Marek Kočiško; Petr Baron; Monika Telíšková; Jozef Török; Anna Bašistová (Advances in Materials Science and Engineering)
The paper presents the results of an experimental study aimed at assessing the correlation between the measurement of dynamic parameters (vibration, high-frequency vibration, and acoustic emission) and the analysis of friction mode and the state of lubrication of the contact surfaces of two gearboxes in the turbo-generator assembly (high-speed single-body steam turbine—gearbox—generator) with the transmission power of no more than 50 MW. The analysis confirmed the assumption of a significant correlation of the monitored high-frequency vibration signal with the unsatisfactory engagement of the gear teeth. Through vibration analysis, an increased level of the tooth vibration component and vibration multiples with increased acoustic emission were identified in gearbox operation. The gear oil of one of the gearboxes examined showed a loss of additive elements in the real operation of the contact surfaces of the teeth engagement. The trend analysis confirmed the complexity of the monitored transmission operation in terms of the friction mode and the influence of the oil quality on the state of the tooth flank microgeometry.